Hypothyroidism and acute kidney injury: An unusual association - De Menezes Neves, Precil Diego Miranda [UNESP]; Bridi, Ramaiane Aparecida [UNESP]; Balbi, André Luis [UNESP]; Ponce, Daniela [UNESP] (BMJ, 2013)
Association between severe hypothyroidism and acute kidney injury (AKI) is rare. A 40-year-old woman presented with 15 days history of generalised muscle pain, weakness, weight gain and oedema. Medical history: hypertension and hypothyroidism. Physical examination: dry skin, peripheral/periorbital oedema, slow thought and speaking, thyroid increased. Laboratory examinations: high levels of creatine kinase , creatinine, uric acid and lactate dehydrogenase. Free T4 was very low (<0.3 ng/dL) and thyroid-stimulating hormone was high (21.7 mIU/mL). Urinalysis showed haem pigment without haematuria. We performed the diagnosis of AKI secondary to hypothyroidism-induced rhabdomyolysis. Intravenous fluids were started, urinary alkalisation and increased l-thyroxine dose replacement. On the day after admission, forced diuresis with furosemide was introduced leading to a progressive improvement of symptoms. Although hypothyroidism and AKI is unusual, it should be suspected in patients presenting decrease of renal function and high creatine kinase in the absence of other causes of rhabdomyolysis.